2014
DOI: 10.1007/s00253-014-5795-3
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of the microbial community in fermented grape marc reveals that Lactobacillus fabifermentans is one of the dominant species: insights into its genome structure

Abstract: Grape marc used for the production of distilled beverages undergoes prolonged storage which allows alcoholic fermentation to occur. Harsh conditions including low pH, limited oxygen and nutrients, temperature fluctuations, and high ethanol concentrations imposed by that environment create a strong selective pressure on microorganisms. A detailed characterization of the bacterial community during two time points of the fermentation process was performed using high-throughput sequencing of the V3-V6 16S rDNA hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 100 publications
2
26
0
Order By: Relevance
“…For instance, Bokulich et al [22] showed that Acetobacter, Gluconobacter, and Gluconoacetobacter are dominant in winemaking processes, whereas Campanaro et al [52] in a grape marc study added that Gluconobacter and Gluconoacetobacter do not survive a prolonged grape marc storage period.…”
Section: Analysis Of Alcoholic Fermentationmentioning
confidence: 99%
“…For instance, Bokulich et al [22] showed that Acetobacter, Gluconobacter, and Gluconoacetobacter are dominant in winemaking processes, whereas Campanaro et al [52] in a grape marc study added that Gluconobacter and Gluconoacetobacter do not survive a prolonged grape marc storage period.…”
Section: Analysis Of Alcoholic Fermentationmentioning
confidence: 99%
“…Instead, they are composed of mixed species of bacteria and eukaryotes, which are thought to be more stable than monospecies films (3,4). This behavior is also the case with microbial communities in food environments (5)(6)(7)(8)(9)(10). In the particular case of olive table fermentations, the presence of polymicrobial communities composed of yeasts and lactic acid bacteria (LAB) attached to both biotic (skin of the olives) and abiotic (inner fermenter walls) surfaces has been reported (11)(12)(13)(14).…”
mentioning
confidence: 97%
“…D. singaporensis, L. fabifermentans, P. dokdonensis, B. argentinensis, L. agarilyticus, and L. algae from the DE group are associated with various metabolic pathways related to skin ulcerations but have not been reported as actual pathogens (Lie et al 1999;Yoon et al 2006;Bercovich et al 2008;De Bruyne et al 2009;Lanzarotti et al 2011;Park et al 2013;Aran et al 2014;Campanaro et al 2014;Treu et al 2014;Yoon et al 2017).…”
Section: Discussionmentioning
confidence: 99%